2021
DOI: 10.1038/s41598-021-97200-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and immunological allergy assessment in cancer patients

Abstract: Cancer is associated with immunodeficiency, while allergies result from immune system hyperactivity mediated by cytokines and immunoglobulins. The purpose of this study was to determine the relationship between immune environment of specific cancers and allergies, emphasizing cytokines related to Th1 and Th2 responses associated with IgE. 80 adults were distributed into two groups: control (n = 20) and cancer (n = 60), distributed in three subgroups (n = 20), head and neck, stomach, and prostate cancers. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 60 publications
0
5
0
2
Order By: Relevance
“…However, Carneiro et al. reported that IL-17 levels in stomach patients were lower than that in the control group (median: 404.2 vs. 573.9 pg/ml, P <0.004) ( 37 ). Our MR analysis found an inverse association of circulating IL-17 levels and the risk of stomach cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, Carneiro et al. reported that IL-17 levels in stomach patients were lower than that in the control group (median: 404.2 vs. 573.9 pg/ml, P <0.004) ( 37 ). Our MR analysis found an inverse association of circulating IL-17 levels and the risk of stomach cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial amount of data, however, has been accumulated, indicating that those working in the occupations with a high degree of fungal exposure generally have a higher rate of cancer [ 5 , 62 , 63 , 64 , 65 ]. In contrast, while somewhat controversial [ 66 , 67 , 68 , 69 , 70 , 71 , 72 ], individuals with allergy-related diseases and asthma have been reported to generally have a lower rate of cancer, including leukemia and a variety of solid tumors, as compared to the general population [ 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ]. Some epidemiological data indicates potential roles for IgE, allergy, and atopy in protecting against certain tumors [ 85 , 86 ].…”
Section: Introductionmentioning
confidence: 99%
“…The presence, specificity, and isotype distribution of Igs in patients with cancer likely have an impact on tumour progression and could potentially inform on early detection of cancer and even predict the survival of the patient [ 6 , 11 ]. Procedures to test the presence of antibodies, especially serum antibodies, are minimally invasive and easy to measure, and for this they harbour potential as biomarkers for cancer.…”
Section: Introductionmentioning
confidence: 99%